Avaliação dos atributos da atenção primária à saúde no município de Campina Grande, Paraíba: Percepção dos profissionais de saúde - Abrantes, Rafaela Simão de (2020)
Primary Health Care (PHC) must assume the basis of the organization of health systems and is considered the best strategy to meet the most frequent health needs of the population, justifying the evaluation of these services for their improvement. Results of studies that assessed PHC suggest gaps in performance and associated factors. The aim of this study is to evaluate the presence and extent of PHC attributes in the city of Campina Grande, Paraíba. This is a cross sectional study, carried out with 202 professionals - doctors, nurses and dental surgeons - selected for convenience, in the Basic Health Units (UBS). The Primary Care Assessment Tool - Brazil (PCATooL-Brazil), professional version, was used, which includes six attributes of PHC (first contact accessibility, longitudinality, comprehensiveness, service coordination, family guidance and community guidance) and provides scores on the your performance. Scores> 6.6 were considered high. Sociodemographic information, training and professional qualification and performance in PHC were also collected between July and December 2019. The data were analyzed using the R Core Team Statistical Software program. In the descriptive analysis, the scores of the attributes were presented as means and medians. Pearson's chi-square test was performed to associate the characteristics of the professionals with the general high and low scores, and T-Student and Mann Whitney tests to verify the scores of the attributes between the three professional categories. The multivariate analysis was based on the prevalence ratios (PR) and their respective confidence intervals (95% CI), estimated using Poisson Regression. A significance level of 5% was adopted for all analyzes. The research was approved by the Research Ethics Committee of the State University of Paraíba (UEPB). The results found a general and essential score of 7.16 and 6.89, respectively. In the analysis by professional category, dental surgeons assigned lower scores on all attributes. Permanent education activity (p <0.05) and medical professionals and nurses in relation to dentists (p <0.05) were associated with the high general score. It is concluded that the PHC aributes are present in the studied city, with the exception of first contact accessibility. The extension of the attributes varied according to the professional category, being lower among dental surgeons. Permanent education stands out as a relevant strategy, since it was associated with a high general score.